The key player in the pathogenesis of environmental influence of systemic lupus erythematosus: Aryl hydrocarbon receptor - Wu, Jingwen; Pang, Tianyi; Lin, Ziyuan; Zhao, Ming; Jin, Hui (Frontiers in Immunology, 2022)
The aryl hydrocarbon receptor was previously known as an environmental receptor that modulates the cellular response to external environmental changes. In essence, the aryl hydrocarbon receptor is a cytoplasmic receptor and transcription factor that is activated by binding to the corresponding ligands, and they transmit relevant information by binding to DNA, thereby activating the transcription of various genes. Therefore, we can understand the development of certain diseases and discover new therapeutic targets by studying the regulation and function of AhR. Several autoimmune diseases, including systemic lupus erythematosus (SLE), have been connected to AhR in previous studies. SLE is a classic autoimmune disease characterized by multi-organ damage and disruption of immune tolerance. We discuss here the homeostatic regulation of AhR and its ligands among various types of immune cells, pathophysiological roles, in addition to the roles of various related cytokines and signaling pathways in the occurrence and development of SLE.